Społeczno-polityczne prawa kobiet we współczesnym Iranie– zarys tematyki - Kuriata, Agnieszka (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2017)
Islamic Republic of Iran is a religious state , in which law is based on sharia law. This article aims to create introduction to wide area of women's rights in contemporary Iran. Author goes into law and sociopolitical issues of women in their everyday life. It also discuses the question of women presence in politics, their right to stand for elcetion as well as elect, and access to education and labour market. Equally important are other forms of social acitivty performed by Iranian woman, which is also point of interest in this article
Keywords: islam; prawo muzułmańskie; Iran; prawa kobiet